( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + … . + ( x 2 7 + x 2 7 1 ) 2
If x 2 + x + 1 = 0 , what is the value of the expression above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That's the short cut I'm looking for! Nice!
x 2 + x + 1 = ( x − ω ) ( x − ω 2 ) so x is ω o r ω 2
ω = ω 2 1 and ω 1 = ω 2
also 1 + ω + ω 2 = 0 and ω + ω 2 = − 1
also ω 3 r = 1 so ω 3 r + 1 = ω
( ω + ω 1 ) 2 + ( ω 2 + ω 4 1 ) 2 + ( ω 3 + ω 6 1 ) 2 + . . . . . . . . . . . . . . . . . . .
we observe terms of form 3 r + 1 and 3 r + 2 and 3 r are 9 each.(i am talking about power of x i.e x , x 2 , x 3 , x 4 , x 5 . . . . )
terms of form 3 r + 1 have value 1 . similarly terms of form 3 r + 2 have value 1 and terms of form 3 r have value equal to 2 2 .
so answer is 9 + 9 + ( 2 ) 2 × 9 = 5 4
Simple to understand! Good!
We will use the fact that if x+1/x=2cosA then x^n + 1/x^n = 2 cos(nA)
Since x^2 + x + 1=0 this implies x+1/x=-1=2cos(2pi/3)
Required answer = 2^2((cos(2pi/3))^2 + (cos(4pi/3))^2+ (cos(6pi/3))^2)*9 =54
x 2 + x + 1 = 0 ⟹ x + x 1 = − 1 . L e t f ( n ) = x n + x n 1 W e o b s e r v e t h a t f { n ≡ 1 ( m o d 3 ) } = − 1 . f { n ≡ 2 ( m o d 3 ) } = − 1 . B u t f { n ≡ 0 ( m o d 3 ) } = 2 . ∴ f ( n ) 2 a r e , 1 , 1 , 4 , r e s p e c t i v e l y . F o r n = 1 , 2 , 3 , . . . 2 7 , t h e r e a r e 3 2 7 = 9 o f e a c h o f t h e t h r e e t y p e s . ∴ t h e S U M A T I O N = 9 ∗ 1 + 9 ∗ 1 + 9 ∗ 4 = 5 4
Problem Loading...
Note Loading...
Set Loading...
My solution is similar to Tanishq's but more elementary as I'm not explicitly using complex numbers. Observe that ( x 2 + x + 1 ) ( x − 1 ) = x 3 − 1 = 0 , so that x 3 = 1 . It follows that x 3 k = 1 , x 3 k + 1 = x , x 3 k + 2 = x 2 for all (positive or negative) integers k . Thus x m + x m 1 = 1 + 1 = 2 when m is divisible by 3 and x m + x m 1 = x + x 2 = − 1 otherwise. Since there are 9 summands of the first kind (with m divible by 3) and 18 of the latter, the answer is 9 × 2 2 + 1 8 ( − 1 ) 2 = 5 4 .